PROTOTYPE ALAT PEMBERITAHUAN KEBAKARAN MENGGUNAKAN MIKROKONTROLER AVR DAN SMS GATEWAY - Sari, Nova Noor Kamala (Universitas Palangka Raya, 2016)
There are several factors causing wildfire such as human error, gas leak, and electric short circuit. Those causes should be rapidly controlled. In case of that urgency, the tools to detect immediate fire is needed to give earlier warning quickly and automatically. In designing the detector,the use of several supporting components is also needed to construct the series of board Microcontroler ATmega16, temperature sensor LM35, fire sensor Flame V2, Modem Wavecom, and Alarm Bazzer, and the additional technology in the form of sms. The results of the prototype is to provide eralier warning via sms and alarm, the warning contains the recent conditation of the temparature. If the system of the micro-controller detects the abnormal temperature from the both sensor, the detector will send the notification to the user. Firthermore, the user directly receive the information and can give the quick responses to protect or to overcome the fire.